1997
DOI: 10.1023/a:1006857520122
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Receptors for advanced glycation end products (RAGE), which bind and internalize AGE-modified proteins formed from oxidation and other products of the nonenzymatic glycation reaction, have been mechanistically implicated in the development of the chronic complications of diabetes. In the present experiments, we sought evidence for the participation of RAGE in diabetic nephropathy by analysis of steady state levels of mRNA encoding RAGE in the renal cortex of a well-defined animal model (the db/db mouse) that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…DPHC treatment did not affect the expression of RAGE mRNA, suggesting that a decrease in the accumulated amount of AGE might contribute to the preventive effects on MGO-induced cytotoxicity. In agreement with this result, it was reported that circulating and tissue levels of AGE-modified proteins were increased in diabetic db/db mice, but RAGE expression levels in the renal cortex were not different between diabetic and nondiabetic littermates [ 67 ].…”
Section: Discussionsupporting
confidence: 84%
“…DPHC treatment did not affect the expression of RAGE mRNA, suggesting that a decrease in the accumulated amount of AGE might contribute to the preventive effects on MGO-induced cytotoxicity. In agreement with this result, it was reported that circulating and tissue levels of AGE-modified proteins were increased in diabetic db/db mice, but RAGE expression levels in the renal cortex were not different between diabetic and nondiabetic littermates [ 67 ].…”
Section: Discussionsupporting
confidence: 84%
“…S2a,b ). Activation of the AGE/RAGE/NFκB pathway may play an important role in the pathogenesis of the DN 26 , 29 . To verify that AGE-RAGE signal activation, we assessed the expression and phosphorylation (activation) status of NFκB subunit p65.…”
Section: Resultsmentioning
confidence: 99%
“…Concentrations of AGE-modified plasma and renal proteins were determined by measurement of fluorescence using an excitation wavelength of 340 nm and an emission wavelength of 415 nm as described elsewhere 29 . Measurement of protein concentration in plasma and in extracts of the renal cortex allowed expression of the data as arbitrary fluorescence units normalized to protein content.…”
Section: Methodsmentioning
confidence: 99%